The Blackwell Encyclopedia of Sociology 2007
DOI: 10.1002/9781405165518.wbeosg056
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, Sexuality and

Abstract: The globalization of sexuality refers to the sexualized and embodied nature of processes associated with the movement of people, capital, and goods across national boundaries. It also refers to how the consciousness of the world as a single place is sexualized. The globalization of sexuality is manifest in a range of processes and phenomena that are often couched and approached in highly emotive terms (e.g., the trafficking of women into prostitution, mail‐order brides, the development of the sex industry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
140
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(148 citation statements)
references
References 9 publications
2
140
0
6
Order By: Relevance
“…These claims are made despite arguments that the resources of such a market are overemphasised (Campbell, 2005) and that the meanings and identity of being a gay male are not universal (Binnie, 2004). In August 2007, a press release [3] was issued by QSoft as a response to Light's (2007) study which suggested that Gaydar potentially, could marginalise and stereotype users through its profiling system.…”
Section: Introducing Qsoftmentioning
confidence: 99%
“…These claims are made despite arguments that the resources of such a market are overemphasised (Campbell, 2005) and that the meanings and identity of being a gay male are not universal (Binnie, 2004). In August 2007, a press release [3] was issued by QSoft as a response to Light's (2007) study which suggested that Gaydar potentially, could marginalise and stereotype users through its profiling system.…”
Section: Introducing Qsoftmentioning
confidence: 99%
“…I have argued that calls to deconstruct and destabilise normative gay and lesbian subjects can remain an emphatic declaration of intent if not supported by a coherent methodology. Replacing 'gay and lesbian' with 'queer' terminology does not represent a way forward, since queer is not inherently a subversive and 'democratic' (Binnie 2004) and the privileged status of English within them, by reminding the reader that languages reflect heterogeneous conceptual world, and that 'a monolingual view of the world is also a monocultural one' (Besemeres and Wierzbicka 2007:xiv). A research agenda sensitive to linguistic and cultural diversity can hopefully avoid unwarranted polarisations between 'East' and 'West', and contribute to a more nuanced understanding of the intersections between the global, the national, the transnational and the local.…”
Section: Discussionmentioning
confidence: 99%
“…Bleys (1996) shows that European representations of nonWestern sexualities constructed the boundaries of a specific 'geography of perversion and desire', which opposed modern, civilised, domesticated 'Western' sexualities to premodern, perverse, exotic sexual 'others'. This kind of Orientalist discourse (Said 1978), pitting the 'progressive' and 'liberated' West against the 'traditional' and 'sexually repressed' East, is by no means confined to the past, as the paradigmatic 'modern homosexual' has been replaced with the 'global gay' (Altman 1996), embodied in new globalising discourses around 'pink dollar' consumerism and LGBT human rights (Binnie 2004;Puar 2007). …”
Section: Lost In Translation: Modernity and The Queer Othermentioning
confidence: 99%
See 2 more Smart Citations